Taking Lessons from CAR-T Cells and Going Beyond: Tailoring Design and Signaling for CAR-NK Cells in Cancer Therapy - Ruppel, Katharina Eva; Fricke, Stephan; Köhl, Ulrike; Schmiedel, Dominik (Frontiers in Immunology, 2022)
Cancer immunotherapies utilize the capabilities of the immune system to efficiently target malignant cells. In recent years, chimeric antigen receptor (CAR) equipped T cells showed promising results against B cell lymphomas. Autologous CAR-T cells require patient-specific manufacturing and thus extensive production facilities, resulting in high priced therapies. Along with potentially severe side effects, these are the major drawbacks of CAR-T cells therapies. Natural Killer (NK) cells pose an alternative for CAR equipped immune cells. Since NK cells can be safely transferred from healthy donors to cancer patients, they present a suitable platform for an allogeneic “off-the-shelf” immunotherapy. However, administration of activated NK cells in cancer therapy has until now shown poor anti-cancer responses, especially in solid tumors. Genetic modifications such as CARs promise to enhance recognition of tumor cells, thereby increasing anti-tumor effects and improving clinical efficacy. Although the cell biology of T and NK cells deviates in many aspects, the development of CAR-NK cells frequently follows within the footsteps of CAR-T cells, meaning that T cell technologies are simply adopted to NK cells. In this review, we underline the unique properties of NK cells and their potential in CAR therapies. First, we summarize the characteristics of NK cell biology with a focus on signaling, a fine-tuned interaction of activating and inhibitory receptors. We then discuss why tailored NK cell-specific CAR designs promise superior efficacy compared to designs developed for T cells. We summarize current findings and developments in the CAR-NK landscape: different CAR formats and modifications to optimize signaling, to target a broader pool of antigens or to increase in vivo persistence. Finally, we address challenges beyond NK cell engineering, including expansion and manufacturing, that need to be addressed to pave the way for CAR-NK therapies from the bench to the clinics.